Case Grammar in the Short Story “Al Malikun Najjar” by Kamil Kailani Based on Charles J. Fillmore's Perspective - Asfiya, Wardatul; Muntaqim Al Anshory, Abdul (Jurnal Pendidikan Indonesia, 2025)
In a short story, the author certainly uses a good and correct language order to make it easier for readers to understand the contents of the carpen. Sometimes the writer also writes dialogs between characters in the storyline. These dialogues or narratives can be analyzed using Charles J Fillmore's theory which divides sentences into two kinds, namely modality and proposition. The purpose of this study is to (1) describe the forms of modality in the short story “Al-Malikun Najjar” based on Charles J Fillmore's theory and (2) describe the forms of proposition in the short story “Al- Malikun Najjar” based on Charles J Fillmore. This research uses a descriptive qualitative approach, which is a research method used to examine the condition of natural objects. where the researcher is the instrument. key. The data collection technique used is by recording and reading. Data were collected by means of: (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion drawing. First, the data were carefully collected and recorded in the short story “Al-Malikun najjar”. This research uses a descriptive qualitative approach, which is a research method used to examine the conditions of natural objects. where the researcher is the instrument. key. The data collection technique used is by recording and reading. Data were collected by means of: (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion drawing. The results of this study are: (1) the form of modality which consists of: Time modality, Adverbial modality, Negation modality, and (2) ten forms of propositions in the short story “Al-Malikun Najjar” which include aggressive cases, time cases, objective cases, location cases, experience cases, and instrument cases